Implementation of generalized predictive control (GPC) for a real-time process control using labview - Mohd. Faudzi, Ahmad 'Athif (2006)
Real-time control is an approach to evaluate process system with real-time parameters by controlling selected variables to accomplish the control objectives. Real-time issues such as rapid testing, nonlinearity and computational problem have led researchers in recent years to do intensive work on development methodologies to enhance control in real-time. Selection of control approaches has also been reviewed to adapt with these real-time issues apart from other strategies. In this research, a predictive algorithm namely Generalized Predictive Control will be evaluated in real-time by applying LabVIEW software as tools for algorithm implementation. LabVIEW is chosen because of its block diagram implementation with simple graphical user interface approach to execute algorithm in real-time faster. Hence, it is essential for complex algorithm to control real-time process system. Coupled-tanks have been identified as process models that are inherently nonlinear and hard to control due to unavailability of the exact models’ descriptions. As for this, real time control will be applied to the coupled tank as the test bed for level control process. Experimental evaluation and comparison of the predictive algorithm performance will be benchmarked against PID control. PC and analogue input output card will be used as the controller and also for data acquisition and realtime data display